Community Service Program: Hygiene and Sanitation of Tempeh Production Houses (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Efforts to develop the level of public health are significant to achieve a better standard of living. Most of the people of Jatimulya sub-district RT 03 RW 08 make their living as Tempeh entrepreneurs. Based on observations related to the sanitary hygiene of Tempeh processing workers, it is still not good, almost all workers do not use gloves or waterproof shoes. One method to achieve this level of public health is by providing the community with understanding, knowledge, and awareness to implement a clean and healthy lifestyle starting from themselves, their families, the school environment, and the wider community. This effort aims to increase people's knowledge and understanding to have self-awareness and potential to maintain health through learning Clean and Healthy Living Behavior (PHBS). The implementation method is by; counseling about PHBS practices at the household level, and Tempeh business outreach about PHBS at the sub-district level, teaching the community about correct hand washing practices, and empowering the community with activities to keep the environment clean. This activity involves the entire community. The results of research activities show that there is a change in attitudes regarding clean and healthy living behavior and a change in people's behavior regarding PHBS and the entire community has been able to wash their hands properly, posters, leaflets and videos with the message of the importance of personal hygiene at work use a rational approach to ensure The target is to gain new knowledge so that it can increase knowledge of the attitudes and practices of processing workers related to the importance of personal hygiene at work